The alchemy of human variation: Race, ethnicity and Manoiloff’s blood reaction - Naidoo, Nicollete P.; Štrkalj, Goran; Daly, Thomas J.M. (Anthropological Review, 2007)
This paper examines the research on race determination conducted by Russian biochemist E.O. Manoiloff in the 1920s. Manoiloff claimed to have discovered a method which detected racial identity of an individual by a simple chemical reaction performed on a subject's blood sample. The method was published in one of the leading anthropological journals and it was not questioned for some time. It is obvious today that Manoiloff's claims were nothing short of ridiculous. The present study, based on the experimental history of sciences, tries to elucidate Manoiloff's procedures and reasons for his ‘success’. His experiments were repeated using both original and modern equipment. It has been demonstrated that Manoiloff's procedures, although rigorous at first glance, were highly arbitrary and methodologically flawed. It would appear that the socio-political and scientific contexts of the early twentieth century which favoured belief in the existence of clearly distinguishable racial types played a crucial role in the initial positive response to Manoiloff's research.